Partial differential equations of mathematical physics - Sobolev, S. L. (Sergei Lvovich), 1908-1989 (Adiwes international series in mathematics., 1964)
Partial Differential Equations of Mathematical Physics emphasizes the study of second-order partial differential equations of mathematical physics, which is deemed as the foundation of investigations into waves, heat conduction, hydrodynamics, and other physical problems.